Glutathione-functionalized magnetic thioether-COFs for the simultaneous capture of urinary exosomes and enrichment of exosomal glycosylated and phosphorylated peptides. Issue 3 (5th January 2022) - Xiong, Fangfang; Jia, Jiaxin; Ma, Jiutong; Jia, Qiong
Abstract : A novel magnetic material, Fe3 O4 @Thio-COF@Au@GSH, was applied to enrich exosomes and exosomal glycosylated and phosphorylated peptides simultaneously. Abstract : Exosomes play an irreplaceable role in physiological and pathological processes, and the study of proteomics (especially protein post-translational modifications, PTMs) in exosomes can reveal the pathogenesis of diseases and screen therapeutic disease targets. The separation and enrichment process is an essential step in mass spectroscopy-based exosomal PTMs studies to reduce sample complexity and ionization-suppression effects. Herein, we designed a novel magnetic zwitterionic material, namely glutathione-functionalized thioether covalent organic frameworks (Fe3 O4 @Thio-COF@Au@GSH), possessing fast magnetic responsiveness, regular porosity, and a suitable surface area. Thanks to the hydrophilicity and charge-switchable feature of GSH, for the first time, both the capture of exosomes from biological fluids and enrichment of the inherent glycoproteins/phosphoproteins in the exosomes were achieved with the same material. Furthermore, the high enrichment capacity was validated by theoretical calculations. The low detection limits (0.2/0.4 fmol for HRP/β-casein), high selectivity (1 : 1000 for HRP/β-casein : BSA molar ratio), and high exosomal glycoproteomics/phosphoproteomics profiling capability proved the feasibility of the developed method. This work provides a new heuristic strategy to solve the problems of exosomal capture and glycoproteins/phosphoproteins pretreatment in exosomal proteomics.